The effect of oxygen content on the temperature dependent tribological behavior of Cr–O–N coatings - Senel, E.; Ürgen, Mustafa Kamil; Ezirmik, V.; Kahraman, Z.; Kazmanli, K. (Elsevier BV, 2009)
CrN, Cr―O―N and Cr―O coatings with different oxygen contents were produced with reactive cathodic arc physical vapor deposition on high speed steel substrates. The temperature dependent friction and wear behaviours of these coatings were investigated within the temperature range of 25-100 °C. The results of the study showed that it is possible to produce CrN coatings with temperature independent, low coefficient of friction (CoF) and wear behavior by introducing oxygen into them. The amount of oxygen in the coating played a critical role on the tribological behavior. Only, in the coatings produced with oxygen content higher than 46%, a temperature independent wear behavior was observed. The structure and chemistry of the coatings and wear tracks were investigated with XRD and micro Raman spectroscopy. The coatings, with an oxygen content higher than 46%, consisted of Cr 2 O 3 and other compounds that are giving broad Raman shifts between 675―834 cm ―1 . With the presence of compounds giving Raman shifts at 675―834 cm ― 1 , in the film and/or in the wear track, it became possible to achieve films with temperature independent, low CoF and wear behavior.